Eksistensi Kesenian Wayang Kulit dalam Menjaga Kerukunan di Desa Sumber Arum Kabupaten Seluma - Ismail, Ismail; Sepri Yunarman; Nurhidayati, Sri Wahyu (Ummul Qura Jurnal Institut Pesantren Sunan Drajat (INSUD) Lamongan, 2025)
Traditional arts such as shadow puppets are a national cultural heritage that has high philosophical value and plays an important role in maintaining social harmony amidst the diversity of society. This study aims to explore how the existence of shadow puppetry contributes to maintaining social harmony in Sumber Arum Village, Seluma Regency. This study uses a qualitative approach with descriptive methods. Data collection techniques were carried out through observation, in-depth interviews, and documentation of traditional leaders, puppeteers, village heads, and local artists. The results show that shadow puppetry has been an important part of community life since 1976, brought by transmigrants from Yogyakarta. Shadow puppet performances are routinely held through activities such as Sedekah Bumi and supported by the establishment of the "Muda Laras" art studio whose members are local youth. These performances are not only a medium of entertainment, but also a means of conveying moral messages, values of tolerance, mutual cooperation, and social solidarity. The conclusion of this study is that the existence of shadow puppetry has a real contribution to maintaining and strengthening social harmony in the community. The noble values embodied in wayang performances, along with the community's participatory process in their implementation, create a harmonious atmosphere and togetherness amidst diversity. This art form serves as a unifying medium, bridging the older and younger generations, and strengthening local cultural identity.